Münchner Leitlinie zu Entscheidungen am Lebensende - Winkler, Eva C. (Ethik in der Medizin, 2012)
Definition of the problem Half of all deaths in Europe are nowadays preceded by decisions about withholding or withdrawing life-sustaining medical treatment. In clinical practice this is often recognized as an ethical challenge, but there are also legal uncertainties and organizational questions among clinicians. Here we present a hospital policy on end-of-life decision making which has the aims of reducing legal uncertainty, sensitizing hospital staff for the ethical dimension of end-of-life decisions, and fostering ethically justified decisions. From an organizational ethics perspective, the policy should provoke reflection and opinion formation on an ethically relevant topic, contribute to quality management in health care and, hence, improve patient satisfaction. Arguments The process of developing, updating, and implementing this hospital policy is presented. The core contents of the policy, illustrated by a decision-making algorithm, including the current state of law, central concepts, and criteria of end-of-life decision making, are also summarized. Finally, the process and content of the policy are scrutinized with regard to the following quality criteria of organizational ethics: deliberative process, transparency, representative composition of the issuing committee, implementation, and evaluation. Conclusion Health care institutions interested in adopting this policy are advised to discuss it in an authorized committee and tailor it to their own specific needs. This may be supported by a prior needs assessment. The committee should represent all those who will be working with the policy later.
Online publiziert: 13. September 2011
Gesehen am 25.06.2018